Genome-Wide Identification, Characterization, and Comparative Analysis of NLR Resistance Genes in Coffea spp. - Santos, Mariana de Lima; Resende, Mário Lúcio Vilela de; Alves, Gabriel Sérgio Costa; Huguet-Tapia, Jose Carlos; Resende, Márcio Fernando Ribeiro de Júnior; Brawner, Jeremy Todd (Frontiers in Plant Science, 2022)
The largest family of disease resistance genes in plants are nucleotide-binding site leucine-rich repeat genes (NLRs). The products of these genes are responsible for recognizing avirulence proteins (Avr) of phytopathogens and triggering specific defense responses. Identifying NLRs in plant genomes with standard gene annotation software is challenging due to their multidomain nature, sequence diversity, and clustered genomic distribution. We present the results of a genome-wide scan and comparative analysis of NLR loci in three coffee species (Coffea canephora, Coffea eugenioides and their interspecific hybrid Coffea arabica). A total of 1311 non-redundant NLR loci were identified in C. arabica, 927 in C. canephora, and 1079 in C. eugenioides, of which 809, 562, and 695 are complete loci, respectively. The NLR-Annotator tool used in this study showed extremely high sensitivities and specificities (over 99%) and increased the detection of putative NLRs in the reference coffee genomes. The NLRs loci in coffee are distributed among all chromosomes and are organized mostly in clusters. The C. arabica genome presented a smaller number of NLR loci when compared to the sum of the parental genomes (C. canephora, and C. eugenioides). There are orthologous NLRs (orthogroups) shared between coffee, tomato, potato, and reference NLRs and those that are shared only among coffee species, which provides clues about the functionality and evolutionary history of these orthogroups. Phylogenetic analysis demonstrated orthologous NLRs shared between C. arabica and the parental genomes and those that were possibly lost. The NLR family members in coffee are subdivided into two main groups: TIR-NLR (TNL) and non-TNL. The non-TNLs seem to represent a repertoire of resistance genes that are important in coffee. These results will support functional studies and contribute to a more precise use of these genes for breeding disease-resistant coffee cultivars.